2003
DOI: 10.7202/006904ar
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Earnings of Visible Minorities in Canada

Abstract: Summary This article presents new evidence on the relative earnings of visible minority immigrant and native-born paid workers in Canada using data from the 1996 Census. Our findings show that labour market disadvantages associated with visible minority status are largely confined to immigrant men. The earnings deficits imputed to minority native-born men and immigrant women are fairly modest, and it appears that native-born women are paid a premium. Among immigrant men, labour market disadvantages a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 19 publications
1
25
0
3
Order By: Relevance
“…These findings are also consistent with previous studies that indicate that visible minority immigrants face greater barriers to labour market integration than do their white counterparts (see Baker and Benjamin, 1997;Hum and Simpson, 1999;Swidinsky and Swidinsky, 2002;Aydemir and Skuterud, 2005 among others).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are also consistent with previous studies that indicate that visible minority immigrants face greater barriers to labour market integration than do their white counterparts (see Baker and Benjamin, 1997;Hum and Simpson, 1999;Swidinsky and Swidinsky, 2002;Aydemir and Skuterud, 2005 among others).…”
Section: Resultssupporting
confidence: 92%
“…Bloom, Grenier and Gunderson, 1995;Reitz, 2001;Frenette and Morissette, 2003;Aydemir and Skuterud, 2005), and that this disadvantage is greater for non-European or visible minority immigrants than for those of European origins (e.g. Baker and Benjamin, 1997;Pendakur and Pendakur, 1998;Hum and Simpson, 1999;Swidinsky and Swidinsky, 2002). Bloom, Grenier and Gunderson (1995) examined the 1971, 1981 and 1986 Censuses and found that while the negative entry effect for European immigrant men was about 1.5 percent, for non-European immigrant men, the entry effect was closer to 22 percent.…”
Section: Previous Researchmentioning
confidence: 99%
“…This illustrates the sensitivity of estimates of labour market discrimination to the econometric technique employed and the efficacy of broadening the notion of discrimination to include occupational segregation. Since previous research has concluded that, of any visible minority, Black men are "most profoundly affected by labour market discrimination" (Swidinsky and Swidinsky, 2002), the Brown, Moon and Zoloth method appears to provide useful complementary evidence to that derived from the Oaxaca-Blinder decomposition method (e.g., Hou and Coulombe, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…D'autres vont plus loin et affi rment que les gains des immigrants diffèrent selon l'origine ethnique, le désavantage étant plus marqué selon l'appartenance aux différents groupes de minorités visibles (Preston, Lo et Wang, 2003 ;Renaud, Piché et Godin, 2003 ;Swidinsky et Swidinsky, 2002 ;Thompson, 2000 ;Basavarajappa et Jones, 1999 ;Hum et Simpson, 1999 ;Pendakur et Pendakur, 1998).…”
Section: Emploi Qualifié Et Immigrationunclassified